Hubungan Kekuatan Otot Lengan dan Fleksibilitas Otot Punggung terhadap Efektivitas Teknik Koshi Guruma - Muhammad Alifi Irsyadillah; Arif Setiawan (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to examine the relationship between arm muscle strength and back muscle flexibility and the effectiveness of the koshi guruma technique among judo athletes. A quantitative approach with a correlational research design was employed. The study involved 20 athletes from Nararya Sport Club Semarang who were selected through purposive sampling based on predetermined criteria. Data were collected using a push-up test to assess arm muscle strength, a V sit-and-reach test to measure back muscle flexibility, and a koshi guruma skill test to evaluate the effectiveness of technique execution. The collected data were analyzed using Spearman Rank correlation and multiple correlation analyses. The findings revealed a significant positive relationship between arm muscle strength and the effectiveness of the koshi guruma technique, as indicated by a correlation coefficient of 0.517 and a significance level of 0.020 (p < 0.05). In contrast, back muscle flexibility did not show a statistically significant relationship with the effectiveness of the technique, with a correlation coefficient of 0.318 and a significance value of 0.172 (p > 0.05). Furthermore, the results of the multiple correlation analysis demonstrated a significant simultaneous relationship between arm muscle strength and back muscle flexibility and the effectiveness of the koshi guruma technique, with an R value of 0.544 and a significance level of 0.039 (p < 0.05). The coefficient of determination (R²) was 0.296, indicating that the two independent variables jointly accounted for 29.6% of the variance in the effectiveness of the koshi guruma technique, while the remaining 70.4% was attributed to other factors beyond the scope of the study.